2020
DOI: 10.1007/s42729-020-00383-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Management Impacts on Nutrient Use Efficiency and Energy, Carbon, and Net Ecosystem Economic Budget of a Rice–Wheat Cropping System in Northwestern India

Abstract: The purpose of this study was to investigate the effect of nutrient management practices on crop productivity, energy use efficiency (E R), greenhouse gas (GHGs) emissions, and carbon (C) and economic yields which impacts the net ecosystem economic budget (NEEB) of worlds' largest rice-wheat cropping system. The effect of different nutrient management strategies (viz. UF control, N, NP, NK, PK, NPK, FYM, N + FYM, and NPK + FYM) on nutrient (N, P, and K) availability, nutrient use efficiency, and yield-scaled g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Nutrient (N/P/K) use efficiency parameters were calculated using the following formulae, as per [25]: where TNUF is the total nutrient uptake of DSR from the fertilized plot (kg ha −1 ), TNUC is the total nutrient uptake of DRS from the control plot (kg ha −1 ), AFN is the amount of applied fertilizer nutrient (kg ha −1 ), GYF is the grain yield of the fertilized plot (kg ha −1 ), and GYC is the grain yield of the control plot (kg ha −1 ). GY is the grain yield (Mg ha −1 ).…”
Section: Nutrient Use Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient (N/P/K) use efficiency parameters were calculated using the following formulae, as per [25]: where TNUF is the total nutrient uptake of DSR from the fertilized plot (kg ha −1 ), TNUC is the total nutrient uptake of DRS from the control plot (kg ha −1 ), AFN is the amount of applied fertilizer nutrient (kg ha −1 ), GYF is the grain yield of the fertilized plot (kg ha −1 ), and GYC is the grain yield of the control plot (kg ha −1 ). GY is the grain yield (Mg ha −1 ).…”
Section: Nutrient Use Efficiencymentioning
confidence: 99%
“…A PFPK of 62.42-191.33 has been reported [64]. In general, the reciprocal internal use efficiency (RIUE) followed the order RIUEN>RIUEK>RIUEP [25]. The RIUE for nitrogen, phosphorus, and potassium was enhanced markedly with STCRbased nutrient management practices, compared to GRD alone.…”
Section: Nutrient Use Efficiency (Nue)mentioning
confidence: 99%
“…In our study, decreasing wheat yield and N use efficiency at higher fertilizer-N application rates can result in large increase in tillering and biomass production [ 79 ] and decrease the vegetative growth of organs [ 80 ], increasing lodging [ 81 ], and parasite susceptibility [ 82 ]. Numerous researchers suggested that a balanced application of fertilization can improve nutrient use efficiency and reduce environmental impacts [ 10 , 83 , 84 ], and that the application of fertilizers (N, P and K) results in higher grain yields [ 30 , 85 , 86 ]. The interaction between K and N, especially available-N and K forms on plant growth and development, has become a focus of research.…”
Section: Discussionmentioning
confidence: 99%
“…enzyme activity, photosynthesis rate) processes of plants, which influencing plant growth [ 6 , 7 ]. Research on N fertilization to cereal crops has been well highlighted because of its essential role in high yielding systems [ 8 10 ], improved dough quality and the potential for environmental impacts due to low N use efficiency [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation